Name-bearing type specimens in the Canadian National Collection of Insects, Arachnids & Nematodes (CNC): Blattodea, Dermaptera, Notoptera, Mecoptera, Megaloptera, Myriapoda, Neuroptera, Odonata, Orthoptera, Phthiraptera, Pseudoscorpiones, Psocoptera, Raphidioptera & Siphonaptera - Lonsdale, Owen; Locke, Michelle M. (Zootaxa, 2018)
A catalogue is provided for the name-bearing types of most of the less diverse arthropod groups deposited in the Canadian National Collection of Insects, Arachnids & Nematodes (CNC). There are 90 name-bearing types of Myriapoda [Chilopoda (3 types), Diplopoda (2)], Arachnida [Pseudoscorpiones (1)], and Insecta [Blattodea (1), Dermaptera (1), Notoptera (3), Mecoptera (3), Megaloptera (2), Neuroptera (11), Odonata (2), Orthoptera (5), Phthiraptera (2), Psocoptera (10), Raphidioptera (1) and Siphonaptera (43)]. Three myriapod syntypes are represented by an unknown number of specimens. Holotypes for Plesiorobius canadensis Klimaszewski & Kevan (Neuroptera) and Sphaeropsocoides canadensis Grimaldi & Engel (Psocoptera) are amber-preserved fossils. Portions of the holotype of Chaetospania assamensis Sakai are considered lost, as are an unknown number of syntype specimens for the centipede species Ethopolys alaskanus Chamberlin and E. integer Chamberlin. Collembola types were treated in Stebaeva et al. (2016), and Araneae, Ephemeroptera, Plecoptera and Trichoptera will be treated in future catalogues, completing inventories for the orders without associated research staff in the CNC. Definitions of relevant type specimens are provided, as is a preliminary summary of all 16,710 name-bearing type specimens held by the CNC, including those of the more diverse orders for which there are associated research staff: Nematoda, Acari, Coleoptera, Diptera, Hemiptera/Thysanoptera, Hymenoptera and Lepidoptera.